PERANAN PERMAINAN BAGI PERKEMBANGAN FISIK MOTORIK BAGI ANAK PENDIDIKAN DASAR - Nur Rosyada; Vianita Solehsi (CV Putra Publisher, 2022)
The purpose of this study was to describe and analyze the gross motor and fine motor phases, to describe and analyze gross motor and fine motor development and to describe and analyze the role of play for physical and fine motor development. This research method uses a qualitative type of literature review research. As for collecting data using books, journal articles, and websites that are relevant to the research title. The results of the study state that aspects of motor development are one aspect of development that can integrate the development of other aspects. Motor physical development is defined as the development of the elements of maturity and control of body movements.